Sex differences in the association between preexisting comorbidities and COVID-19-related symptoms during the COVID-19 pandemic in the Dominican Republic - Wen, Shu-Hui; Chakanika, Beatrice; Rodríguez, Nelson Martínez; Suberví, Katherine Victorio; Pérez Rodríguez, Julia; Yiin, Lih-Ming; Hsieh, Chia-Jung (Frontiers in Public Health, 2025)
BackgroundSex-based differences in the impact of comorbidities on coronavirus disease 2019 (COVID-19) related symptoms remain underexplored due to the predominance of sex-aggregated data. We aimed to examine sex differences in the associations between preexisting comorbidities and COVID-19-related symptoms during the COVID-19 pandemic in the Dominican Republic.MethodsWe conducted a cross-sectional study using a questionnaire survey in the Dominican Republic between September 2021 and December 2021. Data on demographic factors, preexisting comorbidities, and self-reported COVID-19-related symptoms were collected. A multiple logistic regression model was used to separately identify associations between preexisting comorbidities and COVID-19-related symptoms in males and females.ResultsWe included a total of 3,308 eligible individuals. Approximately 25% of the participants had preexisting comorbidities, and 31% of the participants experienced COVID-19-related symptoms. Multiple logistic regression analyses revealed that asthma (OR = 2.15, 95% CI = 1.20–3.85, p = 0.01) was associated with the presence of COVID-19-related symptoms in males. For females, chronic lung disease (OR = 5.39, 95% CI = 1.52–19.18, p = 0.009), hypertension (OR = 1.33, 95% CI = 1.00–1.77, p = 0.047) and diabetes mellitus (OR = 1.70, 95% CI = 1.07–2.71, p = 0.025) were correlated with COVID-19-related symptoms.ConclusionOur study findings observed sex-differences in the associations between preexisting comorbidities and COVID-19-related symptoms. Specifically, we observed that male individuals with asthma and females with chronic lung disease, hypertension, and diabetes mellitus had a greater likelihood of experiencing COVID-19-related symptoms. Future studies are needed to confirm the mechanism underlying these sex differences.